Duplex-specific nuclease signal amplification-based fluorescent lateral flow assay for the point-of-care detection of microRNAs. Issue 2 (9th November 2020) - Wei, Hongjuan; Peng, Yongjin; Bai, Zikun; Rong, Zhen; Wang, Shengqi
Abstract : We demonstrate a fluorescent lateral flow assay combined with duplex specific nuclease signal amplification strategy for high-sensitive point-of-care detection of cancer-related miRNA. Abstract : MiRNAs play important regulatory roles in numerous biological processes and serve as significant biomarkers for the development and prognosis of several diseases. Their unique characteristics, such as short size, high sequence homology among family members, low abundance, and easy degradability, have hindered their specific and highly sensitive detection. Herein, a duplex-specific nuclease (DSN)-assisted target recycling signal amplification-based fluorescent lateral flow assay was demonstrated for the point-of-care detection of cancer-related miRNA-21. In this assay, digoxin/biotin-labeled DNA probes were selectively cleaved by the DSN enzyme in the rounds of hybridization with the miRNA-21 target and cleavage cycle. Subsequently, the resulting mixture, containing the miRNA-21 target and intact and cleaved DNA probes, was loaded onto the lateral flow strip with digoxin antibody-conjugated quantum dot nanobeads and the streptavidin-coated test line. The increase in the proportion of cleaved DNA probes can induce a weakened response signal, which is directly associated with the amount of the miRNA target. Thus, highly sensitive quantification of miRNA-21 was achieved at a low limit of detection of 0.16 pM within 2 h of assay time. Assay specificity toward miRNA-21 was validated by testing several other miRNAs, including let-7b, let-7d, miRNA-141, and miRNA-200a. Moreover, the assay can quantify miRNA-21 spiked in human serum samples with acceptable recovery values, thus indicating its considerable clinical feasibility.